The Level of Teaching Competence in Light of the National Curriculum Standards Among Kindergarten Teachers in the Asir Region - Jafar, Kreemah Ahmad; ALshehri, Salem Rafie (Jazan University Journal of Human Sciences, 2025)
This study looked at how well kindergarten teachers in Asir are performing based on national curriculum standards. It also explored the challenges that make it hard for them to teach according to these standards. The standards include areas like learning approaches, language development, national identity, social studies, emotional and social development, cognitiv processes, Islamic education, and physical health The study also checked if factors like years of experience and academic background affect the teachers' performance. 170 kindergarten teachers from Asir participated in the study. The researchers collected information about their experience, qualifications, and teaching skills, then used a questionnaire to measure their competence based on the national standards.The results showed that teachers had a high level of competence, especially in physical health and development. This was followed by language skills and Islamic education. However, they faced moderate challenges that impacted their ability to fully follow the standards.
Keywords: Teaching Competence; National Curriculum; Kindergarten